Ferrets develop fatal influenza after inhaling small particle aerosols of highly pathogenic avian influenza virus A/Vietnam/1203/2004 (H5N1) - Sosna William A; Tuttle Richard S; Hamilton Sara B; Lednicky John A; Daniels Deirdre E; Swayne David E (Virology Journal, 2010)
Abstract Background There is limited knowledge about the potential routes for H5N1 influenza virus transmission to and between humans, and it is not clear whether humans can be infected through inhalation of aerosolized H5N1 virus particles. Ferrets are often used as a animal model for humans in influenza pathogenicity and transmissibility studies. In this manuscript, a nose-only bioaerosol inhalation exposure system that was recently developed and validated was used in an inhalation exposure study of aerosolized A/Vietnam/1203/2004 (H5N1) virus in ferrets. The clinical spectrum of influenza resulting from exposure to A/Vietnam/1203/2004 (H5N1) through intranasal verses inhalation routes was analyzed. Results Ferrets were successfully infected through intranasal instillation or through inhalation of small particle aerosols with four different doses of Influenza virus A/Vietnam/1203/2004 (H5N1). The animals developed severe influenza encephalomyelitis following intranasal or inhalation exposure to 101, 102, 103, or 104 infectious virus particles per ferret. Conclusions Aerosolized Influenza virus A/Vietnam/1203/2004 (H5N1) is highly infectious and lethal in ferrets. Clinical signs appeared earlier in animals infected through inhalation of aerosolized virus compared to those infected through intranasal instillation.